A Break in the Size–Stellar Mass Relation: Evidence for Quenching and Feedback in Dwarf Galaxies - Nushkia Chamba; Pamela M. Marcum; Amélie Saintonge; Alejandro S. Borlaff; Matthew J. Hayes; Valentin J. M. Le Gouellec; S. Drew Chojnowski; Michael N. Fanelli (The Astrophysical Journal)
Mapping stars and gas in nearby galaxies is fundamental for understanding their growth and the impact of their environment. This issue is addressed by comparing the stellar “edges” of galaxies D _stellar , defined as the outermost diameter where in situ star formation significantly drops, with the gaseous distribution parameterized by the neutral atomic hydrogen diameter measured at 1 M _⊙ pc ^−2 , D _HI . By sampling a broad H i mass range 10 ^5 M _⊙ < M _HI < 10 ^11 M _⊙ , we find several dwarf galaxies with M _HI < 10 ^9 M _⊙ from the field and Fornax Cluster that are distinguished by D _stellar ≫ D _HI . For the cluster dwarfs, the average H i surface density near D _stellar is ∼0.3 M _⊙ pc ^−2 , reflecting the impact of quenching and outside-in gas removal from ram pressure and tidal interactions. In comparison, D _stellar / D _HI ranges between 0.5 and 2 in dwarf field galaxies, consistent with the expectations from stellar feedback. Only more massive disk galaxies in the field can thus be characterized by the common assumption that D _stellar ≲ D _HI . We discover a break in the D _stellar – M _⋆ relation at m _break ∼ 4 × 10 ^8 M _⊙ that potentially differentiates the low-mass regime, where the influence of stellar feedback and environmental processes more prominently regulates the sizes of nearby galaxies. Our results highlight the importance of combining deep optical and H i imaging for understanding galaxy evolution.